Spirituality as The Foundation of The Hierarchy of Needs in The Humanistic Psychology of Abraham Maslow and Sufi Psychology of Said Nursi - Nur Hadi Ihsan; Muhammad Alif Rahmadi; Jamal Jamal (Fakultas Agama Islam Universitas Muhammadiyah Yogyakarta, 2022)
Abraham Maslow’s theory discredits the existence of religion and substitutes it with secular spirituality. It provides a space for anthropocentrism and materialism philosophy, freedom, authorization, and a single human potentiality. On the other hand, Said Nursi’s Sufi Psychology sets religious teachings as the radiance of spirituality. It identifies the genuineness of human beings as creatures who are obedient to God. This study aims to reveal how humanistic psychology and Sufi psychology perceive the need for spirituality by referring to Abraham Maslow and Said Nursi. Researchers identify, select, and formulate relevant and constructive narratives to support each theory stated. They then conducted a deductive content analysis of the references using the available variables, categories, and content tabulations. This research finds that Maslow's spirituality relies on subjective human experience, and life satisfaction can be achieved by maximizing one's potential. On the other hand, Nursi's spirituality is based on the Shari'a and leads to fundamental happiness. For Maslow, the existence of God has been alienated from the human mind, and religion has become a secondary component. At the same time, Nursi has a Tauhidic perspective on reality and believes that religion is the primary guidance of life. Meanwhile, secular spirituality promises nothing but illusory pseudo-happiness. This concept originated from the confusion of Modern Western Psychology on the nature of God, religion, and human psychology. This confusion will vanish if it refers to religious teaching as the ultimate truth. Although both have differences in their ontological nature and conceptual psychological foundations, they both present a similar understanding of recognizing a Higher Entity capable of controlling human life. This entity is called God. In conclusion, Nursi's concept of Tawhid-based spirituality offers a solution to modern man's anxiety, emptiness, and powerlessness of their life problems.